Pérolas hansênicas: relato de caso - PEREIRA JUNIOR, Antonio Carlos Filgueiras (2023)
This paper reports a case of commitment eye by Mycobacterium leprae, the bacterium causing leprosy, a patient coming into the city of Ananindeua, which was submitted to ophthalmologic consultation to evaluate his visual acuity and his retina. Showed up with skin changes and poor visual acuity in both eyes. In ophthalmologic exam the patient had visual acuity only to “vultos” in both eyes. A biomicroscopy noted in the right eye corneal infiltrate higher with the presence of precipitates ceráticos pigmented, "flare" and pearls and absence of pupil. In the left eye corneal infiltrate higher with the presence of precipitates ceráticos pigmented, "flare" and pearls and irianos nodules, absence of pupil. Was the diagnosis of ceratouveite Hansênica, and patient transferred to the Center Marcelo Cândia for treatment of leprosy, then undergo surgical correction of cataract bilaterally as well as iridectomia for biopsy, occurring procedure without complications. The final diagnosis confirmed by baciloscopy of the lymph and histopathology of iris. Currently the patient is in treatment of the changes produced by leprosy, presenting a visual acuity of 20/40 in right left eye and 20/30 in left eye, with correction.